A rapid systematic review of the literature on the association between Salmonella enterica harborage in cattle at various life stages and Salmonella enterica burden at harvest - Ekakoro, John E.; Edache, David; Cernicchiaro, Natalia; Renter, David; Costello, Margaret; Gragg, Sara E.; Ricke, Steven C. (My University, 2024)
Non-typhoidal Salmonella, is a major cause of foodborne illness in humans in the United States leading to about 1.35 million human infections, 26,500 hospitalizations, and 420 deaths (CDC, 2023). Food-producing animals such as cattle are reservoirs of Salmonella (Heredia and García, 2018) posing a serious food safety concern (Xie et al., 2016). Animals that have recovered from initial Salmonella infection may continue to harbor the bacteria in their lymph nodes and internal organs, a phenomenon referred to as carrier status, and may intermittently or continuously shed high numbers of the bacteria in their feces or milk (Nielsen et al., 2004). Salmonella harborage in cattle has been studied by several research groups who have demonstrated the presence of this pathogen in cattle lymph nodes (Brichta-Harhay et al., 2012; Gragg Sara E. et al., 2013; Webb et al., 2017; Wottlin et al., 2022), hence posing a transmission risk to consumers via ground beef (Xie et al., 2016). Cattle type, season, geographic region where cattle farm is located are risk factors for Salmonella harborage in peripheral lymph nodes and feces of cattle at harvest (Webb et al., 2017; Wottlin et al., 2022). In addition to the mentioned risk factors, the life stage of cattle may be an important risk factor for Salmonella harborage. A study conducted in the northeastern United States (Cummings et al., 2009), found wide disparity in the incidence of Salmonella among cattle at different life stages with pre-weaned female calves having the highest incidence and the lowest incidence reported in adult cows. Additionally, calves harvested for veal have been found to harbor Salmonella (Nielsen et al., 2011). Despite the existing literature on Salmonella harborage, we do not have a comprehensive understanding of the link between Salmonella harborage in cattle at various life stages and the burden of Salmonella at harvest (from stunning, skinning, evisceration, chilling to fabrication into beef cuts, ground beef, and other beef products). Given its importance as a foodborne pathogen and the risk of its transmission to consumers through beef products, there is a need for an in-depth understanding of the association between pre-harvest harborage and the impact on post-harvest burden of this pathogen in beef carcasses, ground beef and other beef products. This knowledge will inform efforts aimed at mitigating Salmonella in beef products. This study will review the existing scientific literature to fill this knowledge gap and identify key areas for future research and will be conducted as a collaboration between Kansas State University and the University of Wisconsin-Madison.